Jordan superderivations. II - Maja Fošner (International Journal of Mathematics and Mathematical Sciences)
In a recent paper we have extended the classical Herstein's theorem on Jordan derivations on prime rings to Jordan superderivations on prime associative superalgebras. In the present paper we extend this result to semiprime associative superalgebras.